The effect of sea level rise on flood levels in the Great Brak Estuary: assessing the adequacy of a 5 m setback line - Du Pisani, Julia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.